(untitled) (LACCEI, 2024)
The Mangomarca fog oasis in Lima is an important system of regulation and services that is subject not only to the impacts of climate change, but also to land trafficking, illegal invasions and pollution which has generated a serious environmental deterioration and loss of biodiversity Faced with this situation, the Cesar Vallejo University, within the framework of social responsibility and its interest groups, participates with the community and the Ecotourism Association of the area, to protect the Mangomarca ecosystem, seeking solutions based on nature and alliances collaborations promoting a better quality of life. An analysis of the system that today exerts actions and pressures on the fog oasis of Mangomarca is made challenges are identified in the midst of a covid 19 pandemic that does not end and collaborative strategies for resilience to climate change are developed, in the context of sustainable development